The Marriage at Cana - King, Rosemary (The expository times, 2009)
The article reflects on the miracle performed by Jesus Christ during the wedding at Cana in Galilee, Israel depicted in John, Book of the New Testament of the Holy Scripture. When the hosts of the wedding encountered a problem with shortage of wine, Mary simply told her divine Son Jesus Christ about it and let Him deal with it. It is emphasized that many people never thanked God for all the good things they are enjoying in life. The author encourages people to pray when they have problems and believe that God will do something.